Adolescent–provider relationship and perception of protection of health data: insights from the West Bank – Palestine – a qualitative study - Nour Issa; Maysaa Nemer; Niveen Abu-Rmeileh (International Journal of Adolescence and Youth)
Adolescence is a crucial time for health decisions, where privacy and confidentiality, especially in Palestine, impact adolescents’ willingness to seek healthcare. This study aims to explore Palestinian adolescents’ experiences with health data protection and its impact on seeking healthcare. The findings revealed diverse perspectives on health, healthcare-seeking, and health data protection. Barriers include limited trust in healthcare providers, data security awareness, and privacy concerns, leading to hesitancy in sharing sensitive health information with healthcare providers and thus refraining from consulting them. Our study provides a sense of how Palestinian adolescents perceive privacy and confidentiality in healthcare and its impact on seeking healthcare. Adolescents in the West Bank – Palestine may face health challenges as their hesitation to seek care, driven by privacy concerns and reliance on less reliable health information, increases the risk of engaging in risky behaviours. Interventions and strategies are essential to promote better health outcomes for this population.